Melanoma as a surprising solution to the puzzle of intestinal obstruction - Maksymilian Gajda; Grażyna Kamińska-Winciorek; Iwona Grzesiak; Jerzy Wydmański (Sociedade Brasileira de Dermatologia, 2016)
Abstract We present a case of a 71-year-old man with an advanced melanoma of the right colon. The final diagnosis was determined based on histopathological examination of the material collected during urgent laparotomy performed due to ileus. Although we considered the tumor to be a disseminated primary melanoma of the colon, the possibility of unknown primary origin could not be excluded. Palliative chemotherapy and radiotherapy reduced symptoms associated with the disease and prolonged patient's survival.